The The Effect of Population Pressure on the Erosion Hazard Level of Sub-Watersheds - PAMBUDI, Andi Setyo; KOESTOER, Raldi Hendrotoro Seputro; SUTJININGSIH, Dwita; SOEDARJANTO, Muchamad Saparis (Protection: Journal Of Land And Environmental Law, 2024)
The accuracy of land use and management affects the watershed's or sub-watershed's health, especially upstream. The Lesti sub-watershed in Malang Regency is the upstream part of the Brantas watershed; their land use pattern is always associated with erosion rates, which impact sedimentation in the middle and downstream. When discussing erosion, the rate increase is generally influenced by erodibility, erosivity, length/gradient of the slope, and plant factors/conservation measures. Population pressure has not been discussed much, although the erosion rate affecting sedimentation in the Sengguruh Reservoir as an outlet for the Lesti Sub-watershed has much to do with the Population's activities. People's activity and choice of land use put pressure on the land, affecting the watershed's carrying capacity. Measuring the land's carrying capacity is usually known from the value of existing population pressure and its effect on vulnerability or Erosion Hazard Level (EHL). This study attempted to assess the relationship between erosion hazard levels and population pressure and determine conservation priority areas in the Lesti sub-watershed. This research method was carried out quantitatively, which involved calculating the analysis of population pressure and the EHL obtained spatially from the erosion rate of the Modified Universal Soil Loss Equation (MUSLE) and soil solum. The results showed a similar wedge between high population pressure and severe EHL. This Area is recommended as the most priority location for conservation policies in the Lesti sub-watershed.